Assessment of the clinical and economic impact of advate in prophylactic treatment of hemophilia a patients (Italian Journal of Public Health, 2012)
The objective of this project has been to develop an HTA on Advate, octocog alfa, third-generation ricombinant factor VIII for the treatment and prophylaxis of bleeding episodes in patients affected by Hemophilia A in order to analyse the product’s potentials and limitations in the context of the epidemiological, clinical, economic and organisational situation in Italy.